Hypostomus macushi, a new species of the Hypostomus cochliodon group (Siluriformes: Loricariidae) from Guyana - Armbruster, Jonathan W.; de Souza, Lesley S. (Zootaxa, 2005)
Hypostomus macushi is described as a new species of the H. cochliodon group based on the presence of a light background with widely separated black spots. The only members of the H. cochliodon group with similar coloration are H. cochliodon, H.ericae, H. ericius and H. paucipunctatus. Hypostomus macushi can be separated from H. cochliodon by lacking a longitudinal ridge on the pterotic-supracleithrum and a lack of longitudinal dark stripes; from H. ericius by lacking keels formed from sharp odontodes on the lateral plates; from H. ericae and H. paucipunctatus by lacking a buccal papilla; from H. ericae by having spots in the distal dorsal and caudal fins not combining (vs. spots combining to form wavy lines); and from H. paucipunctatus by having medium to large spots (vs. very small spots). Hypostomus macushi is found in tributaries of the Essequibo and Negro Rivers of Guyana. The range of H. taphorni is additionally expanded to cover much of the Essequibo River basin in Guyana and a single locality in the Takutu River drainage. Addition of H. macushi and H. sculpodon to the phylogeny of the Hypostomus cochliodon group collapsed most of the clades found in a previous analysis. Only the H. cochliodon group, the wood-specializing species, and H. ericius + H. oculeus are supported as clades.Hypostomus macushi é descrito como uma nova espécie do grupo H. cochliodon baseado no padrão de coloração do corpo claro com pontos esparços. Os únicos membros deste grupo com pigmentação similar são H. cochliodon, H.ericae, H. ericius e H. paucipunctatus. H. macushi difere de H. cochliodon pela ausência da crista do pterótico-supracleitro e pela ausência de listras largas; e difere de H. ericius pela presença de quilhas pouco desenvolvidas com odontóides arredondados; de H. ericae e H. paucipunctatus pela ausência de papila bucal; de H. ericae por apresentar máculas na porcão distal dorsal e nadadeira caudal organizados aleatóriamente (vs. máculas arranjadas formando linhas onduladas); e de H. paucipunctatus por porssuir máculas de tamanho médio a grande (vs. máculas diminutas). H. macushi é encontrado nos tributários dos Rios Essequibo e Negro, na Guiana. A distribuição de H. taphorni é expandida para a maior parte da bacia do Rio Essequibo e em uma localidade na drenagem do Rio Takutu. A adição de H. macushi e H. sculpodon na filogenia do grupo H. cochliodon colapsou a maioria dos clados encontrados em um estudo anterior.